Kemampuan Berpikir Kreatif Siswa pada Pembelajaran Auditory Intellectually Repetition - Saputra, Edy; Zulmaulida, Rahmy; Marlina, Marlina (Universitas Dr. Soetomo, 2020)
Abstract This study aimed to determine the students' creative thinking ability through the Auditory Intellectually Repetition (AIR) cooperative learning model in the Arithmetic Series material in the X Science class of Public Senior High School 2 PEUSANGAN. The population in this study were all students of class X Science at Public senior High School 2 PEUSANGAN, Bireuen Regency with research samples was class X IPA 4 as experimental class I, and X IPA 3 as experimental class II, with the total number of students, were 35 for each class which was selected by using purposive sampling. Data analysis was carried out through a quantitative descriptive. To find out the difference in the average, it was used two-sample- t-test. The results of the study by testing the hypothesis using the t-test at a significant level of α = 0.05 obtained t_count> t table, namely 1.70> 1.67, so it was concluded that students' creative thinking ability through Auditory Intellectually Repetition (AIR) cooperative learning model was better rather than students' creative thinking skills through Expository learning models. Keywords: Creative Thinking Ability; AIR Cooperative Model; Expository Learning Abstrak Penelitian ini bertujuan untuk mengetahui kemampuan berpikir kreatif siswa melalui model pembelajaran kooperatif Auditory Intellectually Repetition (AIR) pada materi Barisan dan Deret Aritmetika di kelas X IPA SMA Negeri 2 Peusangan. Populasi dalam penelitian ini adalah seluruh siswa kelas X IPA SMA Negeri 2 Peusangan Kabupaten Bireuen dengan sampel penelitian kelas X IPA 4 sebagai kelas eksperimen I, dan X IPA 3 sebagai kelas eksperimen II, dengan jumlah 35 siswa untuk masing-masing kelas yang dipilih secara purposive sampling. Analisis data dilakukan secara kuantitatif deskriptif. Untuk mengetahui perbedaan rerata digunakan uji t dua sampel. Hasil penelitian dengan pengujian hipotesis menggunakan uji t pada taraf signifikan α=0,05 diperoleh , yaitu sehingga diperoleh kesimpulan bahwa kemampuan berpikir kreatif siswa melalui model pembelajaran kooperatif Auditory Intellectually Repetition (AIR) lebih baik daripada kemampuan berpikir kreatif siswa melalui model pembelajaran ekspositori. Kata Kunci: Kemampuan Berpikir Kreatif; Model Kooperatif AIR; Model Ekspositori